Probing the Structure of Kepler ZZ Ceti Stars with Full Evolutionary Models-based Asteroseismology - Romero, A.; Córsico, A.; Castanheira, B.; Gerónimo, F.; Kepler, S.; Koester, D.; Kawka, Adela; Althaus, L.; Hermes, J.; Bonato, C.; Gianninas, A. (Institute of Physics Publishing, 2017)
We present an asteroseismological analysis of four ZZ Ceti stars observed with the Kepler spacecraft: GD 1212, SDSS J113655.17+040952.6, KIC 11911480, and KIC 4552982, based on a grid of full evolutionary models of DA white dwarf (WD) stars. We employ a grid of carbon–oxygen core models, characterized by a detailed and consistent chemical inner profile for the core and the envelope. In addition to the observed periods, we take into account other information from the observational data, such as amplitudes, rotational splittings, and period spacing, as well as photometry and spectroscopy. For each star, we present an asteroseismological model that closely reproduces their observed properties. The asteroseismological stellar mass and effective temperature of the target stars are (0.632 0.027 ± M☉, 10737 ± 73 K) for GD 1212, (0.745 0.007 ± M☉, 11110 ± 69 K) for KIC 4552982, (0.5480 0.01 ± M☉, 12,721 ± 228 K) for KIC11911480, and (0.570 0.01 ± M☉, 12,060 ± 300 K) for SDSS J113655.17+040952.6. In general, the asteroseismological values are in good agreement with the spectroscopy. For KIC 11911480 and SDSS J113655.17+040952.6 we derive a similar seismological mass, but the hydrogen envelope is an order of magnitude thinner for SDSS J113655.17+040952.6, which is part of a binary system and went through a common envelope phase.